Dithiothreitol‐Measured Oxidative Potential of Size‐Segregated Particulate Matter in Fukuoka, Japan: Effects of Asian Dust Events. Issue 6 (27th June 2019) - Nishita‐Hara, Chiharu; Hirabayashi, Motohiro; Hara, Keiichiro; Yamazaki, Akihiro; Hayashi, Masahiko
Abstract: Oxidative potential is an important property of particulate matter (PM) that has been regarded as a more health‐relevant metric than PM mass. We investigated the oxidative potential of size‐segregated PM and effects of Asian dust events in Fukuoka, western Japan. Aerosol particles with diameters smaller and larger than 2.5 μm (fine and coarse particles, respectively) were collected continually from 16 March through 26 May 2016. The oxidative potential was analyzed using dithiothreitol (DTT) assay; chemical components of PM were also found. Air‐volume normalized oxidative potential quantified by DTT assay (DTTv ) was significantly higher during Asian dust events than during nondust‐event days. The mean DTTv of fine and coarse particles during Asian dust events were, respectively, 1.5 and 2.7 times higher than that during nonevent days. DTTv of fine particles was highly correlated with elements dominated by anthropogenic combustion sources and with the elements emitted from multiple sources including mineral dust and combustion sources. DTTv of coarse particles strongly correlated with the mineral dust derived elements, suggesting concentration of mineral dust particles as an important controlling factor especially for the oxidative potential of the coarse particles. We estimated the contributions of water‐soluble transition metals to the oxidative potential of PM. Water‐soluble transition metals (mainly Cu and Mn) can explain only approximately 37% and 60% of the measured oxidative potential of fine and coarse particles, respectively, suggesting substantial contributions of aerosol components other than water‐soluble transition metals such as quinones and insoluble minerals. Key Points: We investigated effects of Asian dust on the oxidative potential of particulate matter in Japan Air‐volume normalized oxidative potential of particulate matter was significantly higher during Asian dust events than on nonevent days Asian dust storms engender exposure of higher concentrations of particulate matter that have potential to generate oxidizing species